2001
DOI: 10.1023/a:1014995523521
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The recently identified nidogen-2 is a matrix protein showing homology to the well-known basement membrane molecule nidogen-1. Nidogen-1 might well serve as a link between laminin-1 and collagen type IV and thus stabilise certain basement membranes in vivo and play a major role in embryogenesis. However, the exact tissue distribution of nidogen-1 and nidogen-2 during human embryogenesis is still unclear. As a first step towards the elucidation of their possible cell biological functions during human developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Interactions of the NID1 and NID2 proteins with many other matrix components have been demonstrated in vitro , in particular with laminins and collagen IV having the role of a stabilizing bridge ( Figure 5 ) [40] , [43] , [44] . Deletion of either NID1 or NID2 did not reveal alterations in the BM architecture [31] , [45] , [46] and it has been suggested that the two proteins may be partially redundant, each compensating for the contingent lack of the other [45] , [47] ; their tissue-specificity in development has been suggested [31] , [48] , [49] . Nonetheless, mice lacking both nidogens die shortly after birth from lung and heart anomalies, which are directly correlated to BM defects [50] .…”
Section: Resultsmentioning
confidence: 99%
“…Interactions of the NID1 and NID2 proteins with many other matrix components have been demonstrated in vitro , in particular with laminins and collagen IV having the role of a stabilizing bridge ( Figure 5 ) [40] , [43] , [44] . Deletion of either NID1 or NID2 did not reveal alterations in the BM architecture [31] , [45] , [46] and it has been suggested that the two proteins may be partially redundant, each compensating for the contingent lack of the other [45] , [47] ; their tissue-specificity in development has been suggested [31] , [48] , [49] . Nonetheless, mice lacking both nidogens die shortly after birth from lung and heart anomalies, which are directly correlated to BM defects [50] .…”
Section: Resultsmentioning
confidence: 99%
“…While there was a slight reduction in ECFC migration upon BMP7v treatment, it is unlikely that this effect is responsible for the potent anti-angiogenic effect. Despite the lack of overt apoptotic or anti-proliferative markers, cords in vitro were clearly eliminated following BMP7v treatment, as evidenced through persistent nidogen and collagen IV immunostaining (reflecting the maintenance of a “basement membrane”[ 41 ]) in the absence of coincident CD31 immunostaining. One possibility is that BMP7v caused the ECFCs to differentiate into a cell type incapable of supporting cord formation (endoMT) [ 42 ] much like BMP4 which was shown to convert endothelial cells into stem-like cells [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The nidogens bind and form a ternary complex with laminin-1 and collagen type IV, connecting the two networks and stabilizing and maintaining the structure of the basement membrane 13, 1517 . Both nidogens are co-expressed in various tissues and it has been proposed that they fulfill similar, if not identical functions and may also play a compensatory role 18, 19 .…”
Section: Introductionmentioning
confidence: 99%